Mechanism of Bidirectional Leading-Strand Synthesis Establishment at Eukaryotic DNA Replication Origins - Aria, Valentina (Mol Cell, 2019)
DNA replication commences at eukaryotic replication origins following assembly and activation of bidirectional CMG helicases. Once activated, CMG unwinds the parental DNA duplex and DNA polymerase α-primase initiates synthesis on both template strands. By utilizing an origin-dependent replication system using purified yeast proteins, we have mapped start sites for leading-strand replication. Synthesis is mostly initiated outside the origin sequence. Strikingly, rightward leading strands are primed left of the origin and vice versa. We show that each leading strand is established from a lagging-strand primer synthesized by the replisome on the opposite side of the origin. Preventing elongation of primers synthesized left of the origin blocked rightward leading strands, demonstrating that replisomes are interdependent for leading-strand synthesis establishment. The mechanism we reveal negates the need for dedicated leading-strand priming and necessitates a crucial role for the lagging-strand polymerase Pol δ in connecting the nascent leading strand with the advancing replisome.